The inhibited seed germination by ABA and MeJA is associated with the disturbance of reserve utilizations in Astragalus membranaceus. Issue 1 (1st January 2018) - Yang, Nan; Guo, Xiaorui; Wu, Yan; Hu, Xiaohang; Ma, Yuehua; Zhang, Ye; Wang, Hongzheng; Tang, Zhonghua
ABSTRACT: Astragalus membranaceus is a major traditional Chinese medicinal plant. Here, we investigated the mobilizations of seed reserves during its germination and post-germination growth, as well as the effects of exogenous abscisic acid (ABA) and methyl jasmonate (MeJA). It was found that both starch and protein were rapidly mobilized during the seed germination. However, lipid was mostly utilized during the post-germination. Exogenous ABA and MeJA treatments significantly inhibited the germination and post-germination growth. Meanwhile, the treatments decreased the weight of mobilized seed reserves and seed reserves utilization efficiency, retarded the mobilizations of protein and lipid, and led to excessive consumption of carbon energy. Moreover, the treatments changed fatty acid compositions in cotyledons, with the decreasing of the double bond index and average carbon chain length. This study will help us to understand the inhibition mechanism of exogenous ABA and MeJA on the germination and post-germination growth of A. membranaceus .